The minipig as an alternative non-rodent model for immunogenicity testing using the TNFα blockers adalimumab and infliximab. (January 2014) - van Mierlo, Geertje J. D.; Cnubben, Nicole H. P.; Wouters, Diana; Wolbink, Gerrit Jan; Hart, Margreet H. L.; Rispens, Theo; Ganderup, Niels-Christian; Kuper, C. Frieke; Aarden, Lucien; Penninks, André H.
Abstract Immunogenicity is a major issue of concern for monoclonal antibodies used in human diseases and is by default mainly determined in non-human primates (NHP), as target molecules are considered most similar in NHP compared to human. In this manuscript the predictive value of immunogenicity testing in minipigs for human safety is evaluated, as the immune system of the pig is functionally similar to that in other mammalian species. Adalimumab and infliximab (both monoclonal antibodies blocking TNFα) were used as model substances. Female Göttingen minipigs (4/group) were treated every other week with low (0.1 mg/kg), mid (1.0 mg/kg), or high dose (5 mg/kg) adalimumab or 5 mg/kg infliximab subcutaneous (SC) over a period of 8 weeks. After first and last dosing, pharmacokinetic analysis was performed. Anti-drug antibodies (ADAs) were measured on several time points. Furthermore, hematology, clinical chemistry, body weight, clinical signs, and histopathology of several organs were evaluated. No signs of toxicity of the treatments were observed in the limited organs and tissues collected. Eleven out of 12 minipigs treated with adalimumab elicited a detectable ADA response. Induction of ADA was correlated with decreased plasma levels of adalimumab. Infliximab clearance was comparable after first and last dose. Therefore, the presence of ADA directed to infliximab was considered highly unlikely. It was concluded that the minipig and NHP showed comparable suitability for immunogenicity prediction in humans. More studies with other biopharmaceutical products are needed to strengthen the status of the minipig as an alternative model for immunotoxicity testing including immunogenicity.